Peran Kepala Sekolah dalam Meningkatkan Kepuasan Layanan Siswa di SMP Negeri 9 Palembang - Dina Nur Azizah; Ade Akhmad Saputra (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This research seeks to depict and examine the principal's contribution to achieving student service satisfaction at SMP Negeri 9 Palembang. The study adopts a descriptive qualitative approach, collecting data through semi-structured interviews, direct field observation, and document analysis. Informants included the school principal, teaching staff, administrative personnel, and students. Data processing employed the Miles and Huberman model, encompassing data reduction, presentation, and verification. Findings reveal that the principal of SMP Negeri 9 Palembang has implemented all seven EMASLIM functions comprehensively and in an integrated manner: as educator, manager, administrator, supervisor, leader, innovator, and motivator. As an educator, the principal consistently conducts professional teacher development via internal training and direct classroom visits. As a manager, school resources are handled with careful planning involving all school stakeholders. As administrator, the principal ensures orderly, transparent, technology-enabled administrative management. As a supervisor, academic supervision is carried out systematically with constructive feedback. As a leader, a service excellence culture is cultivated through exemplary conduct. As an innovator, creative, digitally-based learning approaches are developed. As a motivator, genuine appreciation and personal attention are consistently extended to all school members. The implementation of these seven functions demonstrably contributes to student service satisfaction, encompassing all five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Professional, collaborative, innovative, and sustained school leadership constitutes the primary driver of lasting student service satisfaction.   Keywords: School Principal, EMASLIM, Student Service Satisfaction, SERVQUAL, Education Quality